Actividades desarrolladas por el grupo de yuca en Bolivar y Secretaria de Fomento Agropecuario y Minero - Arrieta B., J.M. (International Center for Tropical Agriculture, 1990)
Regional trials assessing promising cassava clones are listed as well as 2 cassava seed production projects, carried out by the cassava team on Colombia's Atlantic Coast with the support of the Secretaria de Fomento Agropecuario y Minero of the department of Bolivar. Regional trials have been conducted in the municipalities of Villanueva, Mahates, Calamar, and Magangue; data on the percentage of germination are given for the trials conducted in Mahates and Calamar. One of the seed production projects includes 23 promising clones and the other, seed production of cassava var. P-12; both projects were carried out at the Zambrano Regional Farm. (CIAT)